RISK ASSESSMENT AND BUSINESS IMPACT ANALYSIS AS A BASIS FOR THE DRAFTING DISASTER RECOVERY PLAN AT UPT-TIK OF XYZ UNIVERSITY - Laqma Dica Fitrani (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2022)
Disasters can come at any time, cannot be determined when, how they occur, how long and how big the impact they have. Disaster Recovery Plan is a plan prepared by the organization in dealing with disasters, the procedures and what steps must be carried out is described in this document. As the basis for the drafting of the document, two important things are required including several risk assessments which analyze all possible threats and business impact analysis which analyze the impact of the disasters on business activities in an organization. This research was conducted at UPT-TIK (Technical Implementation Unit of Information and Communication Technology) of XYZ University. The results of this study were the risk assessment and business impact analysis which form the basis of the drafting of disaster recovery plan document which include the team responsible for disaster recovery planning.